PENERAPAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALULINTAS TERHADAP PENEGAKAN HUKUM BAGI PELANGGARAN BERLALU LINTAS PENGENDARA BENTOR DI KABUPATEN HALMAHERA UTARA - Selfianus Laritmas; Ruslan Sabtu (Jurnal Akrab Juara, 2018)
Abstract Bentor is short for Becak Motor which is a tricycle from Tobelo. According to the data obtained from the Tobelo City Traffic Unit and the Pehubungan Service, the number of traffic violations committed by the bombing vehicle amounted to 70 cases of violations by 2015 and traffic accidents involving the collision vehicle which amounted to 39 cases of traffic accidents in 2015 The problem discussed in this paper is how the application of the Law for Violations against Terrorism? And What is the sanction for the riders who committed the traffic violation according to the rule of law applicable This research was conducted by using the type of juridical Normative legal research. so the source of the Law material is analyzed is the legal material by using Approach of Law and Approach case. Against the results of the study. Keywords: Implementation of the Act